African customary marriage in Kenya: a case for notification and consent regarding subsequent marriages - Narikae, N. (Strathmore University, 2024)
The Marriage Act, 2014 is the regime of law that primarily regulates the regime of marriage in Kenya. This Act provides for Customary polygamous marriages, from their inception to their dissolution. The Marriage Act, 2014, however, is quiet on the matter of notification and consent of subsequent marriages in Customary polygamous marriages. This study purposes to examine whether the lack of a provision requiring the mandatory notification and consent of a current wife or wives of subsequent marriages in Customary marriages violates Article 45(3) of the Constitution of Kenya and Section 3(2) of the Marriage Act. The study plans to achieve this purpose by pursuing set objectives. The study will examine the legal framework governing Customary polygamous marriages in Kenya, the application and interpretation of these provisions, as well as the realisation of equality in Customary polygamous marriages. The study also seeks to analyse the effect of the absence of a notification and consent clause regarding subsequent marriages in the Marriage Act, 2014, on the equality of parties in Customary polygamous marriages. This author will undertake a desk-based approach to conduct this research. Primary and secondary sources will be used in this paper, including various pieces of legislation and journal articles, among others. This paper’s hypothesis is that the absence of a provision requiring the mandatory notification and consent of a current wife or wives of subsequent marriages, does indeed violate the equality of parties in Customary marriages. This work then intends to recommend that an amendment is made to the Marriage Act, 2014, to incorporate a provision requiring the mandatory notification and consent of a current wife or wives of subsequent marriages in Customary marriages. In order to realise the equality aims of Article 45(3) of the Constitution of Kenya and Section 3(2) of the Marriage Act, and further achieve substantive equality and equity in Customary polygamous unions.
Full - text Undergraduate research project